Obinutuzumab as treatment for ANCA-associated vasculitis. (27th December 2021) - Amudala, Naomi A; Boukhlal, Sara; Sheridan, Brittany; Langford, Carol A; Geara, Abdallah; Merkel, Peter A; Cornec, Divi
Abstract: Objectives: Rituximab is a standard of care therapy for patients with ANCA-associated vasculitis. When rituximab is contraindicated, or in the case of refractory disease, other treatments are needed. Obinutuzumab is another anti-CD20 antibody for the treatment of haematological malignancies that may induce a deeper B cell depletion compared with rituximab. This article reviews three cases of patients with ANCA-associated vasculitis who were treated with obinutuzumab due to their history of anaphylactic reactions to rituximab. Methods: Case series of three patients with ANCA-associated vasculitis treated with obinutuzumab. Results: One female patient with microscopic polyangiitis and two male patients with granulomatosis with polyangiitis received obinutuzumab. The treatment was well-tolerated in all patients despite previous anaphylactic reaction to rituximab. Treatment with obinutuzumab was effective in (i) inducing disease remission, (ii) inducing total B cell depletion, and (iii) resulting in undetectable serum titres of ANCA. All three patients were re-treated with obinutuzumab for maintenance of remission. Conclusion: Obinutuzumab appears to be a safe and efficacious therapy for patients with ANCA-associated vasculitis who have had refractory disease or a history of anaphylaxis to rituximab. Prospective studies comparing rituximab to obinutuzumab in ANCA-associated vasculitis patients are warranted.